2016
DOI: 10.1039/c6cc00194g
|View full text |Cite
|
Sign up to set email alerts
|

Triple-enzyme mimetic activity of nickel–palladium hollow nanoparticles and their application in colorimetric biosensing of glucose

Abstract: We demonstrate that nickel-palladium hollow nanoparticles (NiPd hNPs) exhibit triple-enzyme mimetic activity: oxidase-like activity, peroxidase-like activity and catalase-like activity. As peroxidase mimetics, the catalytic activity of NiPd hNPs was investigated in detail. On this basis, a simple glucose biosensor with a wide linear range and low detection limit was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 146 publications
(70 citation statements)
references
References 26 publications
1
68
0
Order By: Relevance
“…The fluorescence intensity gradually decreased as the concentration of SA Co-MoS 2 continued to increase (Fig. 2d), which further indicated that the introduction of SA Co exhibited ·OH scavenging properties rather than generating ·OH [46][47][48].…”
Section: The Peroxidase-like Activity Of Sa Co-mosmentioning
confidence: 77%
“…The fluorescence intensity gradually decreased as the concentration of SA Co-MoS 2 continued to increase (Fig. 2d), which further indicated that the introduction of SA Co exhibited ·OH scavenging properties rather than generating ·OH [46][47][48].…”
Section: The Peroxidase-like Activity Of Sa Co-mosmentioning
confidence: 77%
“…Herein, ZIF‐8 was chosen as a support for enzyme immobilization to establish a mimic multi‐enzyme system. NiPd hollow nanoparticles, which exhibiting outstanding peroxidase‐like catalytic activity, were successfully immobilized both inside of the ZIF‐8 crystal lattices and on the outer surfaces. The obtained ZIF‐8(NiPd) also possessed excellent property of peroxidase mimic.…”
Section: Figurementioning
confidence: 99%
“…[8] Herein, ZIF-8 was chosen as as upport for enzyme immobilization to establish am imic multi-enzyme system. NiPd hollow nanoparticles,w hich exhibiting outstanding peroxidase-like catalytic activity, [9] were successfully immo-bilized both inside of the ZIF-8 crystal lattices and on the outer surfaces.T he obtained ZIF-8(NiPd) also possessed excellent property of peroxidase mimic. With glucose oxidase (GOx) and NiPd hollow nanoparticles being immobilized simultaneously on ZIF-8, an artificial enzyme system GOx@ZIF-8(NiPd) nanoflower was prepared for tandem catalysis.T he cascade reaction for the visual detection of glucose was successfully combined into one step.Inaddition, due to the competition reactions of electro-catalytic oxygen reduction and glucose oxidation, the GOx@ZIF-8(NiPd) modified glassy carbon electrode (GCE) exhibits quiet different electrochemical performance toward H 2 O 2 and glucose.…”
mentioning
confidence: 99%